2022
DOI: 10.1200/jco.21.02373
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Child-Pugh Dogma in Hepatocellular Carcinoma

Abstract: The albumin-bilirubin (ALBI) score may be a more objective and sensitive method of assessing liver function in patients with hepatocellular carcinoma than the Child-Pugh score, the current standard approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Very early stage (0) HCC is defined as a solitary HCC ≤2 cm without vascular invasion or extrahepatic spread and early stage ( A ) as a solitary HCC irrespective of size or as a multifocal HCC up to 3 nodules (none of them >3 cm) without macrovascular invasion or extrahepatic spread, in patients with preserved liver function and eastern cooperative oncology group PS 0–1. Recently, the ALBI (albumin‐bilirubin) score has been developed as an HCC‐specific improvement of the Child‐Pugh score to reflect the severity and hence the prognosis of cirrhosis 3,4 . Indeed, the limitations of the Child‐Pugh scoring system include the subjectivity of assessment of ascites and encephalopathy, the interdependence of the five parameters, the absence of some important prognostic parameters such as renal function, and the lack of specificity for different disease etiologies.…”
Section: Early‐stage Hepatocellular Carcinoma (Barcelona Clinic Liver...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very early stage (0) HCC is defined as a solitary HCC ≤2 cm without vascular invasion or extrahepatic spread and early stage ( A ) as a solitary HCC irrespective of size or as a multifocal HCC up to 3 nodules (none of them >3 cm) without macrovascular invasion or extrahepatic spread, in patients with preserved liver function and eastern cooperative oncology group PS 0–1. Recently, the ALBI (albumin‐bilirubin) score has been developed as an HCC‐specific improvement of the Child‐Pugh score to reflect the severity and hence the prognosis of cirrhosis 3,4 . Indeed, the limitations of the Child‐Pugh scoring system include the subjectivity of assessment of ascites and encephalopathy, the interdependence of the five parameters, the absence of some important prognostic parameters such as renal function, and the lack of specificity for different disease etiologies.…”
Section: Early‐stage Hepatocellular Carcinoma (Barcelona Clinic Liver...mentioning
confidence: 99%
“…1,2 Tumor staging is key for treatment and prognosis, as well as the assessment of liver cirrhosis in term of liver function and presence of portal hypertension. The Barcelona Clinic Liver Cancer (BCLC) staging system links tumor features, underlying liver disease, and progression free survival (PS) with prognosis and treatment guidelines for HCC (3). In 2022, the BCLC group updated their treatment algorithm, incorporating an expert clinical decision-making component and the concept of treatment stage migration (TSM), a situation wherein the treatment modality normally recommended for a more advanced stage is chosen (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a review of the literature revealed more than 30 versions of the Child-Pugh score such that consistent scoring was difficult to achieve. 2 To this extent, the ALBI score is a simply ‘refined’ version of the Child-Pugh score that excludes redundant features thereby and avoids the inconsistencies inherent in the Child-Pugh grading.…”
Section: Introductionmentioning
confidence: 99%
“…The granularity of the ALBI score permitted the detection of the small changes in liver function in patients with compensated cirrhosis that the Child-Pugh score was not sensitive enough to detect. This is particularly important in an era when the liver function of patients with HCC has been steadily improving, 2 , 3 so that most patients with HCC have no liver (dys)function according to Child-Pugh score. 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation